2008
DOI: 10.4085/1062-6050-43.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a Career in Athletic Training: Exploring the Perceptions of Potential Recruits

Abstract: Context:The success of any academic program, including athletic training, depends upon attracting and keeping quality students. Therefore, understanding potential recruits' perceptions of athletic training is important.Objective: To (1) gain insight regarding undergraduate students' decisions to enter or not enter an athletic training education program (ATEP), and (2) examine potential athletic training recruits' perceptions of the roles and responsibilities of certified athletic trainers.Design: We used a des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
119
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(126 citation statements)
references
References 25 publications
(24 reference statements)
6
119
1
Order By: Relevance
“…The semistructured format of the interviews allowed the researcher to ask the participants to expand on answers or to ask follow-up questions for further detail. The questions were devised based on the work of researchers examining initial socialization 4 of current students and persistence 6 of senior AT students. Examples of interview questions are provided in the Table. The interview questions were examined by an experienced qualitative researcher for content and pilot tested with a recently certified athletic trainer for clarity; the researcher and athletic trainer were not authors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The semistructured format of the interviews allowed the researcher to ask the participants to expand on answers or to ask follow-up questions for further detail. The questions were devised based on the work of researchers examining initial socialization 4 of current students and persistence 6 of senior AT students. Examples of interview questions are provided in the Table. The interview questions were examined by an experienced qualitative researcher for content and pilot tested with a recently certified athletic trainer for clarity; the researcher and athletic trainer were not authors.…”
Section: Methodsmentioning
confidence: 99%
“…Time constraints and an interest in a different career were found to be barriers to choosing AT. 4 Although light has been shed on the factors persuading potential recruits to enter the profession of AT 4 and persist to the senior year, 6 the reasons some students graduate from ATEPs and others leave them before completion remain unclear. No researchers have sought data from recent graduates to determine reasons for their successful persistence.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it represents the largest clinical employment setting for ATs 4 and, therefore, a setting of great interest for ATs. Investigators have suggested that ATs enter the profession because of their attraction to sports and their desire to help people, 5 and some select the setting because of the competitive atmosphere and collegiality of coworkers. 6 However, what makes these dedicated ATs remain in the profession and accept the low pay, long hours, and work-family conflict that lead many others to leave or change job settings?…”
mentioning
confidence: 99%